Solitary pulmonary capillary hemangioma presenting with a ground glass opacity: A case report & literature review. (2020) - Komatsu, Teruya; Hara, Akira; Date, Naoki; Fujinaga, Takuji; Kato, Tatsuo
Highlights: Solitary pulmonary capillary hemangioma (SPCH) is a rare benign lung tumor. SPCH presents with a ground glass opacity on CT scan. Preoperative definitive diagnosis as SPCH is a real challenge. Immunohistochemical staining is essential for diagnosis as SPCH. Abstract: Introduction: Solitary pulmonary capillary hemangioma (SPCH) is a rare benign lung tumor that clinically resembles early lung cancer and precancerous pulmonary lesions that present with similar imaging manifestations. Presentation of case: The patient was a 54-year-old Japanese man who was referred to Nagara Medical Center with a ground glass opacity (GGO) lesion within the right upper lung that was incidentally detected on computed tomography. After 8 months of follow-up, video-assisted thoracoscopic segmental resection of the right upper lobe was performed with diagnostic and therapeutic intent. Pathologic examination of the resected specimen demonstrated thickening of the alveolar septum caused by the proliferation of capillary vessels. This lesion was positive for CD31 and CD34 and negative for thyroid transcription factor-1 and cytokeratin on immunohistochemical staining. The tumor was diagnosed as SPCH pathologically. Discussion: When radiological examination demonstrates a GGO in the lung, SPCH must be considered as one of the differential diagnoses. For a definitive diagnosis, pathological examination of a surgically resected specimen must be conducted. Conclusion: This study describes a case of SPCH and a review of the literature.